Sérgio Abreu: os fundamentos de uma escola violonística - Morais, Luciano [UNESP] (Univ Estadual Parana, Escola Musica & Belas Artes Parana, 2023)
This article investigates the possibilities in which the work of Sergio Abreu as interpreter can give the main structure the foundations of a guitar school. It is based on data collected in my master dissertation, published in 2007, but only here structured in terms of 3 aspects threated as foundations: sonority, rhythm and process of interpretation. This article contains a short analyse of interpretation's history, the oscilations of different performance's poetics and discuss in which sense the step forward to systematization the poetics of a great interpreter is important to democratization of musical knowledge. This step is strongly attached to University's capacity of researching and produce critical foundations in art as human knowledge.
Keywords: performance; musical interpretation; guitar schools; guitar; Sergio Abreu